Analisis Pendapatan Asli Daerah (PAD) Kota Mataram Provinsi Nusa Tenggara Barat - Alwi, Muhammad; Yudha S, I Dewa Ketut; Dema Alkandia, Lalu (Jurnal Ekonomi dan Bisnis, 2017)
The purposes of this research are analyse effectivity of the yeals of The Regional tax, regional retribution and The Regional origin income. To analyse The regional finance independence and decentralization degree. The main contribution that dominant to bafferMatarams PAD source from regional tax income that in average has contribution 48,15 % and other income source of PAD has average contribution 35,83 %, while The regional retribution has contribution 12,66 % to PAD and The yeals of The severed Regional Managing has average contribution 3.31 % in period of 2012 to 2015. The Effectivity degree that very effevctive in years of 2012 to 2014 and in 2015 they are in effective category. The ability of Regional Finance in period of 2012 to 2015 included In Low category. Base on The relation pattern of The Central Government and Regional Government Known that in 2012 they have instructive relationship that show that the role of the central gavernment more dominant than Regional government. (mean the Regional Government has not ability to apply Regional otonomy). In 2013 to 2015 the relationship pattern between Central and Regional Government show consultative pattern that mean that the Intervency of the Central Government start to decrease because the Regional Governmenbe assumed little more be able to apply Regional Otonomy. Mataram Fiscal desentralisation degree include in category of lack ability of regional finance in periode of 2012 to 2015. It shows that Mataram regional finance very dependent to Central and Province income source